Transformasi Zakat Digital dan Peran BAZNAZ dalam Penguatan Ekonomi Umat di Indonesia - Tika Diliana (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Zakat is an Islamic economic instrument that has strategic potential in supporting poverty alleviation and strengthening the economic empowerment of the ummah. In Indonesia, the significant potential of zakat has not yet been fully optimized to promote inclusive and sustainable economic development. This study aims to analyze the transformation of zakat management in Indonesia and its role in strengthening the community’s economy from the perspective of Islamic economics. This research employs a qualitative approach using a literature review and document analysis of zakat regulations, reports from zakat management institutions, and relevant academic literature. The results show that the transformation of zakat management through institutional strengthening, digitalization, and integration with economic empowerment programs has improved the effectiveness of zakat distribution. However, efforts to optimize the role of zakat still face structural, regulatory, and coordination challenges among stakeholders. This study emphasizes the importance of applying the maqashid al-shariah approach in zakat management so that zakat functions not only as a charitable instrument but also as a productive and sustainable one. Keywords: zakat, Islamic economics, community economy, maqashid al-shariah, Indonesia.